Prospective study on ocular findings in acute Puumala hantavirus infection in hospitalised patients. Issue 4 (1st August 2010) - Hautala, Nina; Kauma, Heikki; Vapalahti, Olli; Mähönen, Saara-Mari; Vainio, Olli; Vaheri, Antti; Hautala, Timo
Abstract : Aims: To appraise the ocular manifestations of Puumala hantavirus evoked haemorrhagic fever with renal syndrome nephropathia epidemica (NE) and to clarify the mechanisms of ocular changes in the largest series of patients examined to date. Methods: 92 eyes of 46 patients with serologically proven NE were examined during the acute phase and after clinical recovery. Ocular symptoms were recorded, and visual acuity, refraction, intraocular pressure and ocular dimensions were evaluated. Results: 88% of the patients experienced decreased intraocular pressure (IOP) (p<0.001), 87% reduced visual acuity, 87% conjunctival chemosis, 82% thickening of the lens (p<0.05), 78% myopic shift (p<0.001), 64% shallowing of the anterior chamber (p<0.05) and 52% shallowing of vitreous length (p<0.05) during the acute phase compared with that measured after clinical recovery. In all, 70% of the patients reported ocular symptoms. Conclusion: Ocular symptoms and disturbances are common in acute NE, and the symmetry of the ocular changes reflects the systemic nature of the disease. A decrease in IOP and myopic shift mainly due to thickening of the lens are evident in acute disease. The myopic shift only partially explains the visual disturbances supporting the possible multifactorial origin of the ocular findings in patients with NE.